Victorian Women’s Resistance Against Patriarchy in the Selected Series of The Enola Holmes Mystery by Nancy Springer - Putri , Anandita Indah; Seswita (LingoLitera, 2025)
This research examines the resistance of women in the Victorian period against patriarchy in the selected series of The Enola Holmes Mystery written by Nancy Springer. The aims of this research are to find patriarchal values shown by the male characters and society towards women and to reveal the way women characters resist against the patriarchal values in the Victorian period. In analyzing this research, the writer uses feminist literary criticism, especially radical feminism by Marilyn French and is supported by M. H. Abrams’ mimetic approach. In presenting the data, this research uses descriptive methods and qualitative research. As the result of the analysis, the writer finds four forms of patriarchal values shown in the selected series The Enola Holmes Mystery by male characters and society towards women. It consists of ruled by the elite, limitations in women’s education, women have no rights in property, and women have to get married. The writer also discovers that female characters’ resistance against patriarchy in four ways, such as disguise and dress reform, specific knowledge for women, open a service with male name, and gaining their freedom by escape from the patriarchal environment. This research concludes that Springer delivers patriarchy—the system constructed by society—was mostly beneficial for men than women despite the fact that they consider the system as the best solution for women to settle for a better life precisely reflects Victorian society.